Investigation of the Role of Digital Marketing, Competitive Advantage and Digital Business Strategy on Financial Performance - Praditya, Rayyan Aqila (UJoST- Universal Journal of Science and Technology, 2024)
This research was carried out to examine the influence of competitive advantage and digital business strategy on financial performance which is moderated by digital marketing in micro, small and medium enterprises. This research uses a purposive sampling technique. In this research there are three independent variables, namely competitive advantage, managerial capability, operational capability, as well as one moderating variable, namely digital marketing, and one dependent variable, namely financial performance. In terms of collecting data, this research was carried out using a questionnaire, the scale used in compiling this questionnaire was a 4-point Likert scale with 1 = strongly disagree and 4 = strongly agree. Questionnaires were distributed to MSME players. The questionnaire is made in Softcopy/Google Form form. This research tested the data using SmartPLS version 3 software. This research focused on the target sample, namely Micro, Small and Medium Enterprises (MSMEs) with a total of 345 research samples. The data obtained using the 18 questions in the questionnaire will be analyzed descriptively, then convergent validity tests and discriminant validity tests and reliability tests will be carried out. The results of this research found that competitive advantage has a positive and significant effect on financial performance, managerial capability has a positive and significant effect on financial performance, operational capability has a positive and significant effect on financial performance. On the other hand, digital marketing is unable to moderate the influence of competitive advantage on financial performance and digital marketing is unable to moderate the influence of operational capability on financial performance. However, digital marketing is able to moderate the influence of managerial capability on financial performance.